Determinan Produk Domestik Bruto Indonesia - Silatul Azizah; Muhammad Khoirul Fuddin (Jurnal Ilmu Ekonomi, 2023)
The purpose of this study is to identify and analyze the impact of foreign direct investment (PMA), domestic investment (PMDN), total exports and external debt on Indonesia's gross domestic product. This study uses World Bank data and secondary data sources from previous research journals. The data used in this study are time series data covering 32 years from 1990 to 2021. Data were analyzed by multiple regression analysis with Eviews. The analysis results show that foreign investment (PMA), domestic investment (PMDN), total exports and external debt have a significant impact on Indonesia's gross domestic product.